An evaluation of participation in a schools-based youth mental health peer education training programme. Issue 2 (2nd April 2016) - O'Reilly, Aileen; Barry, James; Neary, Marie-Louise; Lane, Sabrina; O'Keeffe, Lynsey
Abstract: The use of peer education has been well documented within the discipline of health promotion, but not within the youth mental health domain. This paper describes an evaluation of an innovative schools-based peer education training programme that involved preparing young people to deliver a mental health workshop to their peers. Participants ( n = 30) were recruited from five post-primary schools in Ireland. After each training session ( n = 4), participants completed a questionnaire assessing their reactions to training. Participants also completed measures of self-esteem, help-seeking, mental health knowledge and skills at their first and final training session, and at the end of the programme. Significant changes in participants' presentation skills, mental health knowledge and beliefs about help-seeking were observed. Participants also reported that training was well facilitated and well timed. Overall, findings indicate participation in a schools-based mental health peer education training programme is enjoyable and beneficial for young people.